Effects of Plasma Immersion Ion Implantation (PIII) of nitrogen on hardness, composition and corrosion resistance of Ti-6Al-4V alloy - Silva, Leide Lili G. da; Ueda, Mario; Silva, Maria M. da; Codaro, Eduardo N. (FapUNIFESP (SciELO), 2006)
Ti-6Al-4V samples have been treated by PHI processing at different temperatures (400-800°C), treatment time (30-150 min) and plasma potential (100 and 420 V). Hardness measurements results showed an enhancement of the hardness for all implanted samples. XRD results detected the Ti 2N phase and the best corrosion resistance was found for the samples processed at higher temperature and lower PIII time.
Keywords: Corrosion; Hardness; Plasma immersion ion implantation; Ti-6Al-4V; X-ray diffraction